High glucose-induced PLCG1 histone acetylation to promote ferroptosis by LAMP2A/HSPA8 in a diabetic nephropathy model - Ge, Jun; Wang, Zhenzhen; Xu, Ting; Jiang, Ruifeng; Zhang, Xuefeng (Frontiers in Pharmacology, 2026)
Diabetic nephropathy (DN) is one of the most prevalent microvascular complications of diabetes mellitus. In the present study, the effects of PLCG1 DN, as well as its underlying molecular mechanisms associated with ferroptosis, were investigated. Single-cell RNA sequencing data and bioinformatic analyses were employed to support these experimental findings. For in vivo experiments, a DN model was established in C57BL/6 mice via streptozotocin injection. For in vitro investigations, NRK-52E cells were exposed to 20 mmol/L d-glucose to induce a DN-like cellular phenotype. PLCG1 mRNA expression levels were upregulated in DN patients, compared with the normal group. Elevated serum PLCG1 mRNA expression in DN patients correlated with increased urinary creatinine (Cre), blood urea nitrogen (Bun), and 24 h urinary microalbuminuria (mAlb) levels. The mRNA and protein expression levels of PLCG1 m in tissues were significantly upregulated in the mouse DN model and high glucose-induced NRK-52E. Single-cell analysis was performed to detect PLCG1 expression in renal cells of the DN model. Additionally, high glucose exposure induced PLCG1 histone acetylation in the DN model. Sh-PLCG1 alleviated DN progression and reduced oxidative stress in the mouse model. Mechanistically, PLCG1 increased mitochondria-dependent ferroptosis in the DN model. PLCG1 is interlinked with LAMP2A and facilitates the ubiquitination of LAMP2A. Specifically, PLCG1 upregulation enhanced K48-linked ubiquitination of LAMP2A protein in high glucose-induced NRK-52E cells. Ultimately, PLCG1 inhibited the LAMP2A/HSPA8 signaling pathway in the DN model. Our study identifies PLCG1 as a novel regulatory target that inhibits the LAMP2A/HSPA8 signaling pathway. This inhibition promotes mitochondrial oxidative stress, which in turn increases cellular ferroptosis and accelerates the progression of DN. Importantly, PLCG1 holds promise as a critical clinical biomarker for diagnosing DN. It may serve as a potential therapeutic target to mitigate glucose-induced ferroptosis, with implications for the management of not only DN but also other diabetes-related complications.